2022
DOI: 10.17352/ojtm.000021
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of malaria parasitemia in people living with HIV/AIDS in Kumba, Cameroon

Abstract: Background: Malaria parasitemia and HIV infections are globally important public health concerns. People residing in regions where these two infections are endemic are prone to develop co-infection. Sub-Saharan Africa has the greatest burden of both diseases and Cameroon particularly the South West Region has been reported as one of the regions with the highest malaria and HIV prevalence. Hence, there is a need for continuous monitoring and epidemiologic inquiry to generate updated data on the burden of malari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Te result of a previous study showed a prevalence of 90.3% malaria infection among feverish patients in the Kumba health district [23], while among HIV patients, the prevalence is around 27.2% [24]. However, the prevalence of malaria among pregnant women reported by Asoba and collaborators is 43.2%, 25.2%, and 6.8% in the frst, second, and third trimester of pregnancy, respectively [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Te result of a previous study showed a prevalence of 90.3% malaria infection among feverish patients in the Kumba health district [23], while among HIV patients, the prevalence is around 27.2% [24]. However, the prevalence of malaria among pregnant women reported by Asoba and collaborators is 43.2%, 25.2%, and 6.8% in the frst, second, and third trimester of pregnancy, respectively [25].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, to achieve the zero-malaria elimination goal [17], efective tools for malaria diagnosis are needed as clinical diagnosis of this infection remains the key, before making an informed choice on antimalarial medication. It is therefore critical to assess current malaria diagnostic tools at the national level, particularly in resource-limited settings, to determine which tool is more suitable for the detection of malaria infection among pregnant women, as accurate diagnosis of this infection must be followed by immediate treatment, as studies have shown that malaria, particularly in pregnancy, is associated with postpartum complications such as mastitis [18], and excessive uterine blood loss [19]. Tis will guide policy on the clinical management of pregnant women and strategy toward the elimination of malaria in pregnancy.…”
Section: Introductionmentioning
confidence: 99%